113 Changes In Stffness Of Patellar Tendon In Athletes With Tendinopathy And Their Relationships With Pain And Dysfunction. (5th September 2014) - Zhang, Zhi-Jie; Ng, Gabriel Yin-fat; Lee, Wai-Chun; Fu, Siu Ngor
Abstract : Introduction: Patellar tendinopathy (PT) is one of the most common knee disorders among athletes. Changes in elasticity of the painful tendon and how these relate to the pressure pain and dysfunction remain unclear. Therefore, the present study aimed to compare the elastic properties of patellar tendons between athlete with and without unilateral PT and to examine its association with pressure pain and dysfunction Methods: Thirteen male athletes with unilateral PT (age 22.9 ± 4.6 years, height 1.8 ± 0.5m and weight 76.2 ± 6.3 kg, duration of symptom 22.6 ± 22.3 months) and 20 healthy control subjects (age 24.9 ± 4.4 years, height 1.82 ± 0.60m and weight 73.4 ± 7.9 kg) joined in this study. Supersonic shear imaging technique was used to measure the elastic properties of the proximal part of the patellar tendon (SuperSonic Imagine, Aix-en-Provence, France). The mean value of Young's modulus within the region of interest (Figure 1 ) was computed by the ultrasound system. Shear elastic modulus was calculated by dividing the Young's modulus by 3 (Royer et al . 2011). The ratio of mean shear elastic modulus between the painful and non-painful knee was expressed as elastic ratio in athletes with unilateral PT. The intensity of pressure pain and dysfunction were quantified with a 10-lb force to the most painful site and the Victorian Institute of Sport Assessment-patella (VISA-P) questionnaire (Visentini et al . 1998), respectively. Results: In athletes with unilateral PT, the painful tendons had higher shear elastic modulus (43.6 ± 17.9 kPa) than the non-painful side (25.8 ± 10.6 kPa) (by 68.9%; p < 0.05) or the dominant side of the healthy controls (27.5 ± 11.3 kPa) (by 58.5%, p < 0.05). Significant correlations were found between tendon shear elastic modulus ratio and the intensity of pressure pain ( rho = 0.62; p = 0.024) and VISA-P scores ( rho = -0.61; p = 0.026) (Figure 2 ). Discussion: Athletes with unilateral PT had stiffer patellar tendon on the painful side than the non-painful side and the dominant side of healthy athletes. A higher ratio of elastic modulus between the painful and non-painful knee is related with a greater intensity of pressure pain and a lower VISA-P score. Such findings suggest that an increase in tendon stiffness in athletes with unilateral patellar tendinopathy is associated with the tendon pain and dysfunction. References: Royer et al . J Acoust Sco Am. 2011;129(5):2757–2760 Visentini et al . J Sci Med Sport. 1998;1(1):22–28